2011
DOI: 10.1590/s1806-83242011000500002
|View full text |Cite
|
Sign up to set email alerts
|

Timing of fluoride toothpaste use and enamel-dentin demineralization

Abstract: It is well established that fluoride (F) prevents caries development by inhibiting demineralization and enhancing remineralization processes. However, it is not known which of these protective mechanisms is more important. In this double-blind, crossover in situ study conducted in three phases of 14 days each, 12 volunteers wore palatal appliances containing enamel and root dentin slabs, on which biofilm was allowed to accumulate under exposure to 20% sucrose solution 8×/day. F toothpaste was used once a day, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 23 publications
2
13
0
6
Order By: Relevance
“…Thus, despite the fact that dentine mineral is more soluble than enamel [Hoppenbrouwers et al, 1987], and also considering that the cariogenic challenge was carried out 8 times per day, the fluoride present in dentifrice was able to reduce caries progression on this substrate. The importance of FD used at frequencies of once [Kusano et al, 2011] or 3 times a day [Hara et al, 2003;Cenci et al, 2008;Vale et al, 2011] 139 root-dentine demineralization was already known and was confirmed by this study.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Thus, despite the fact that dentine mineral is more soluble than enamel [Hoppenbrouwers et al, 1987], and also considering that the cariogenic challenge was carried out 8 times per day, the fluoride present in dentifrice was able to reduce caries progression on this substrate. The importance of FD used at frequencies of once [Kusano et al, 2011] or 3 times a day [Hara et al, 2003;Cenci et al, 2008;Vale et al, 2011] 139 root-dentine demineralization was already known and was confirmed by this study.…”
Section: Discussionsupporting
confidence: 82%
“…FD is able not only to reduce caries progression on sound enamel-dentine surfaces ('preventive effect'), but also able to remineralize preexisting caries lesions ('therapeutic effect'). These effects can be influenced by certain factors, such as the fluoride concentration [Walsh et al, 2010], the time of day of FD use [Kusano et al, 2011] and …”
mentioning
confidence: 99%
“…Surface hardness data were taken as the only indicator of mineral loss [Cury et al, , 2010Kusano et al, 2011;Vale et al, 2011] in this study since, as shown in figure 1 b, the area of hardness loss was not sensitive to levels above 250 ppm F. Surprisingly, given its central role in the mechanism of F in reducing caries [Margolis and Moreno, 1990;Vogel et al, 1990;Vogel, 2011], overnight biofilm fluid F levels only increased about twice with the use of the Ca prerinse, and this increase was not significantly higher (p = 0.068) than the 250 ppm F rinse alone. Only the 1,000 ppm F rinse produced a 4× significant increase in this parameter.…”
Section: Discussionmentioning
confidence: 99%
“…O fluoreto atua no processo de desmineralização e remineralização. A remineralização ocorre quando os níveis de fluoreto na saliva e no biofilme se encontram supersaturados em relação ao esmalte, mesmo em pH crítico 12 . A presença constante do fluoreto (principalmente o fluoreto presente no creme dental) é responsável pela formação de fluoreto de cálcio, que atuará nas superfícies do esmalte, dentina e cemento durante o processo de desmineralização e remineralização 13,14 .…”
Section: Variáveisunclassified